Global cross-sectional survey on higher education institutions: Analysing the assessment of instrument for evaluating academic expertise on teaching, research and community service - Kurniawan, Deny; Samsura, D. Ary A.; van Deemen, A.M.A. (Faculty of Social and Political Science, Universitas Airlangga, 2024)
Globally, the discussion on expertise assessment in higher education institutions has long been a topic in academic literature. However, there is currently no specific measure of academic expertise based on the roles of academics in carrying out their core functions, such as teaching, research, and community service. A recent literature review proposed twenty-nine academic expertise criteria in assessing the three academic tasks. The present study conducted a validity test of these proposed criteria by employing exploratory factor analysis and principal axis factoring. The study sample comprised three hundred and thirty-one respondents, who were gathered through a worldwide survey. The results indicate that the division of the three academic functions is shown in the final model of the measure. This model consists of three factors, each encompassing various indicators of teaching, research, and community service. The study contributes to the validitation of the academic expertise criteria, which can be further used in developing the expertise scale adjusted to higher education institutions.